2024
DOI: 10.2514/1.c037508
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Overwing and Underwing Nacelle Aeropropulsion Optimization for Subsonic Transport Aircraft

Jai Ahuja,
Chung Hyun Lee,
Christian Perron
et al.

Abstract: This research compares a forward-mounted overwing nacelle configuration to a conventional underwing nacelle for a single-aisle transport aircraft. We focus on characterizing the impact of the overwing placement on cruise fuel burn. To this end, we optimize both configurations under similar constraints and design processes. We use coupled computational fluid dynamics and propulsion cycle analysis with Gaussian process-based adaptive sampling in a multistage design process. The particular overwing design has a 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…It was found that the optimal overwing configuration exhibits at least a 2% increase in drag compared to the conventional installation, thus appearing to be unfavorable in aerodynamic terms. Similar analysis and general outcomes are also proposed in [86,87]. However, the potential benefits that can be obtained in other regards, such as propulsive efficiency, landing gear weight reduction, reduced risk of FOD (foreign object damage [88]) or simplification of high-lift systems, make the overwing assembly interesting for further investigation and successive detailed optimizations.…”
Section: Unconventional Uhbr Turbofan-airframe Installationsmentioning
confidence: 59%
“…It was found that the optimal overwing configuration exhibits at least a 2% increase in drag compared to the conventional installation, thus appearing to be unfavorable in aerodynamic terms. Similar analysis and general outcomes are also proposed in [86,87]. However, the potential benefits that can be obtained in other regards, such as propulsive efficiency, landing gear weight reduction, reduced risk of FOD (foreign object damage [88]) or simplification of high-lift systems, make the overwing assembly interesting for further investigation and successive detailed optimizations.…”
Section: Unconventional Uhbr Turbofan-airframe Installationsmentioning
confidence: 59%